The sun god and the savior : the Christianization of the Nahua and Totonac in the Sierra Norte de Puebla, Mexico - Stresser-Péan, Guy (Mesoamerican worlds., 2009)
This translation presents two decades of fieldwork in the Sierra Norte de Puebla, Mexico, where Native pre-Hispanic pagan beliefs blended with traditional Catholic evangelization from the 16th century and the more recent intrusion of modernism.